2019
DOI: 10.1371/journal.pone.0226620
|View full text |Cite
|
Sign up to set email alerts
|

Copy number-based quantification assay for non-invasive detection of PVT1-derived transcripts

Abstract: BackgroundOne of the most important susceptibility loci for cancer is the 8q24 human chromosomal region. The non-protein coding gene locus plasmacytoma variant translocation 1 (PVT1) is located at 8q24 and is dysregulated in prostate cancer. PVT1 gives rise to multiple transcripts which may have different functions. Here, we describe a real-time quantitative polymerase chain reaction (qPCR)-based assay for copy number-based quantitation of PVT1 exons 4A, 4B, and 9 to enable accurate, reproducible, and quantifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…PVT1 promotes proliferation, invasion, and metastasis, and promotes epithelial to mesenchymal transition in PCa ( Chang et al 2018 ). Though the role of PVT1 is well-established in different cancers and other diseases, very few reports are available on the alternatively spliced transcripts of PVT1 ( Guo et al 2017 , Pal and Ogunwobi 2019 ). We previously demonstrated that PVT1 exon 9 is associated with aggressive PCa in men of African ancestry ( Ilboudo et al 2015 ).…”
mentioning
confidence: 99%
“…PVT1 promotes proliferation, invasion, and metastasis, and promotes epithelial to mesenchymal transition in PCa ( Chang et al 2018 ). Though the role of PVT1 is well-established in different cancers and other diseases, very few reports are available on the alternatively spliced transcripts of PVT1 ( Guo et al 2017 , Pal and Ogunwobi 2019 ). We previously demonstrated that PVT1 exon 9 is associated with aggressive PCa in men of African ancestry ( Ilboudo et al 2015 ).…”
mentioning
confidence: 99%
“…The PVT1 gene is differentially expressed among populations [ 127 ]. Furthermore, quantification of PVT1 expression pattern reveals variations between tissue types with maximal expression in ovaries, lymph nodes and bone marrow and moderate levels of expression in the colon [ 128 ]. Of note, the PVT1-217 transcript is the most abundant in the gastrointestinal tract mucosa [ 115 ].…”
Section: The Role Of Pvt1 In the Diagnosis Treatment And Prognosimentioning
confidence: 99%
“…High expression of specific splice variants like PVT1 -214 is associated with poor overall survival and acquisition of stem-cell like properties including invasion and cell migration [ 137 ]. Furthermore, downstream targets of PVT1 such as miR-26b could provide both a mechanism as well as more specific biomarker readouts of PVT1 activity in CRC [ 128 ]. Poor overall survival with elevated PVT1 expression as well as increased cell proliferation, invasion and metastasis has been shown in further studies [ 138 ].…”
Section: The Role Of Pvt1 In the Diagnosis Treatment And Prognosimentioning
confidence: 99%
“…Primers for PVT1 exons 4A, 4B, and 9 were designed using Primer3Plus. The assay was performed as previously described (17). Concentration of PCR products were measured spectrophotometrically using NanoDrop ® ND100 (Thermo Scientific NanoDrop Products, Wilmington, Delaware) in nanograms per microliter and converted to copies per microliter using the formula y copies ml = ½x ng ml  10 −9 ½pcDNA vector and 273 301 j j130 DNA bps  660 !…”
Section: Copy Number-based Quantification Assaymentioning
confidence: 99%
“…In particular, PVT1 exon 9 was shown to be significantly overexpressed in moAA with aggressive PCa ( 14 ). The promise of these potential biomarkers to improve the clinical diagnosis of PCa, among this most vulnerable population group, was subsequently elevated by the development of a non-invasive copy number-based quantification assay for detecting PVT1-derived transcripts from prostate tissues, serum, and urine samples ( 17 ). Whereas expression levels of PVT1 exons 4A, 4B, and 9 are promising biomarkers in their own right, it is reasonable to expect that a single numeric score that combines information from all two or more transcripts would be a more robust and easier to use diagnostic tool for clinicians.…”
Section: Introductionmentioning
confidence: 99%